Extraction of thorns of ceiba petandra for phytochemicals studies - Noor Asikin, Ibrahim (2015)
Thorns of Ceiba petandra (kekabu plant) is widely used in complementary medicine and has been recommended for the treatment of many diseases such as bronchitis, diarrhoea and skin disease. The thorn of its extract via soxhlet extraction was investigated for optimum operating condition of extraction process and major phytochemical constituent presence (flavanoids, alkaloids and tannins). Methanol and ethanol were used as a solvents in the extraction process with vary the solid to solvent ratio (w: v); 1:10, 1:15 and 1:20. The phytochemical constituents were investigated by using standard procedure and also Gas Chromatography Mass Spectrometry (GC-MS) analysis is only for the optimum condition. The phytochemical analysis revealed that the presence of alkaloid in the entire sample while tannins and flavanoids at solid to solvent ratio in a range of 1:10 to 1:15 for both type of solvents. Based on Gas Chromatography Mass Spectrometry (GC-MS) analysis have prove that the extracted oil by using methanol contain high amount of active compound compare to sample extract using ethanol. This is due to the polarity of the solvents. Results showed that the methanol extract was found to be generally more effective than ethanol extract with solid to solvent ratio is 1:15.